New Versions of the Sermons from the Pandects of Antiochus in the Church Slavonic Prologue - Čistiakova, Marina (Knygotyra, 2023)
The Pandects, an anthology of passages from the Holy Scripture and the writings of the Church Fathers, was compiled in Medieval Greek in around 620 by Antiochus, a monk of the Laura of Mar Saba, at the request of hegumen Eustachius of the Monastery of Atalina. In the 10th century, this collection was translated into the Church Slavonic language in Bulgaria and soon became known in Kyivan Rus’. No later than in the 1160s, fragments of the Pandects were included in the Synaxarion or the Prologue, a calendar collection of the lives of saints and sermons. The didactic part of the Expanded edition of the Prologue was supplemented for the first half of the year with 21 carefully edited passages from the Pandects. During the 14th‒17th centuries, scribes revised the translation of the Pandects again. The subject of this study is the new versions of the Pandects of Antiochus in comparison with the traditional synaxarian sermons from this source. When examining about 100 copies of the Prologue from the autumn-winter half of the church year, dating back to the 14th‒17th centuries, 6 such articles were found. In the Moscow and Kirill-Belozersky editions of the Prologue, which belong to the Moscow literary tradition, I found two new versions (A Sermon on Fasting and on Prayer, A Sermon on if one Loves the World). The fragments of the Pandects were copied from the source in their entirety, without introducing significant changes. In the manuscript tradition of the Grand Duchy of Lithuania (GDL), and later also of the Polish-Lithuanian Commonwealth (PLC), more new variants of the sermons appeared. In the Navahrudak edition, in the two varieties of the Expanded edition and in the Museum edition, four traditional Prologue articles were edited (A Sermon on Eloquence, A Sermon on Dreams, A Sermon on Fasting and on Prayer, A Sermon on if one Loves the World). The writers used a special technique of segmenting the sermons and amending their style. It is possible to conclude that the 10th century translation of the work of monk Antiochus underwent a greater transformation in the literary tradition of the GDL than in the Grand Duchy of Moscow. Ukrainian scribes played a special role in the reception of the Pandects of Antiochus in the lands of the GDL and later in the PLC.
Keywords: textual studies; source studies; manuscript; sermons; translation; edition; Pandects of Antiochus, Prologue; Grand Duchy of Lithuania; Polish- Lithuanian Commonwealth